A brief questionnaire for assessing patient healthcare experiences in low-income settings. - Webster, Tashonna R; Mantopoulos, Jeannie; Jackson, Elizabeth; Cole-Lewis, Heather; Kidane, Lillian; Kebede, Sosena; Abebe, Yigeremu; Lawson, Ruth; Bradley, Elizabeth H (International journal for quality in health care : journal of the International Society for Quality in Health Care / ISQua, 2011)
The aim of this study was to develop and to assess the validity and reliability of two brief questionnaires for assessing patient experiences with hospital and outpatient care in a low-income setting.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Ambulatory Care; Attitude to Health; Ethiopia; Female; Focus Groups; Health Care Surveys; Hospitals; Humans; Male; Middle Aged; Poverty; Professional-Patient Relations; Quality of Health Care; Questionnaires; Young Adult